Comparison of the efficacy of intravenous oxycodone versus morphine on postoperative pain following orthopaedics surgery under general anaesthesia - Sim, Chua Boon (2021)
The devastating outcome of orthopaedic surgical site infections (SSI) are largely preventable if its risk factors, causative organisms and antimicrobial susceptibility patterns in the regional area are known. We conducted a retrospective study to address the lack of epidemiological and microbiological data on orthopaedic SSI in Malaysia. All the 80 patients diagnosed and treated for microbiologically proven orthopaedic SSIs in a tertiary hospital in Malaysia from April 2015 to March 2019 were included in a 1:2 case control study. The prevalence of SSI in clean and clean-contaminated surgeries was 1.243%, which is consistent with most of the studies worldwide, but is low compared to other studies done in Malaysia. The most common type of orthopaedics SSI was internal fixation infections (46.25%). Obesity and tobacco use were found to be significant risk factors of orthopaedic SSI. The most common perioperative prophylaxis used was IV cefuroxime. Majority of the cases (86.5%) received prolonged prophylactic antibiotics. The most common causative agent was Staphylococcus aureus (31.25%), followed by Pseudomonas aeruginosa (26.25%) and Enterobacter spp (7.5%). Methicillin-resistant Staphylococcus aureus (MRSA) accounted for 20% of the S. aureus infections. Up to 19.4% of the Gram negative organisms are multidrug resistant. The prevention of SSI in orthopaedic practice, its prevalence and trends in microbiological profile are related to the management of the risk factors, the appropriate use of prophylactic antibiotics and implementation of infection control measures. A more definitive and larger study in the country is needed to address these issues. We also investigated the role of stingless bee honey as a potential topical agent for the treatment of orthopaedic SSI, to take advantage of its anti-bacterial and anti-biofilm properties. In-vitro synergistic testing was conducted to test honey-antibiotic combinations against MDR Gram Negative and Gram positive organisms. At 5% concentration, stingless bee honey can be safely used as an adjunctive topical agent, without any antagonistic effect with systemic antibiotics